Puerto Rico bélico - Todd, Roberto H. (My University, 2015)
Artículo relacionado a asuntos políticos.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Yager, Arthur, 1858-1941